2021
DOI: 10.1111/ejn.15248
|View full text |Cite
|
Sign up to set email alerts
|

Impact of daytime light intensity on the central orexin (hypocretin) system of a diurnal rodent (Arvicanthis niloticus)

Abstract: The neuropeptide orexin/hypocretin is implicated in sleep and arousal, energy expenditure, reward, affective state and cognition. Our previous work using diurnal Nile grass rats (Arvicanthis niloticus) found that orexin mediates the effects of environmental light, particularly daytime light intensity, on affective and cognitive behaviours. The present study further investigated how daytime light intensity affects the central orexin system in male and female grass rats. Subjects were housed for 4 weeks in 12:12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 101 publications
1
1
0
Order By: Relevance
“…Using the diurnal grass rat model of SAD we demonstrated that early morning BLT given daily for 4 weeks leads to changes in the expression of neuroinflammatory and neuroplasticity markers in corticolimbic brain regions involved in regulating affective and cognitive functions. Consistent with our previous findings in grass rats housed in winter- or summer-like lighting conditions [ 54 , 90 ] or following a BLT paradigm [ 52 ], the effects of BLT are brain region-specific and differ between males and females. The results from our present and previous studies provide novel insights into how seasonal light conditions and light therapy influence a variety of neural functions including neuropeptides and neurotransmitter systems, neuroinflammation, and neuroplasticity with concomitant effects on numerous behavioural outcomes highly relevant to SAD and other depressive disorders in humans [ 41 ].…”
Section: Discussionsupporting
confidence: 91%
“…Using the diurnal grass rat model of SAD we demonstrated that early morning BLT given daily for 4 weeks leads to changes in the expression of neuroinflammatory and neuroplasticity markers in corticolimbic brain regions involved in regulating affective and cognitive functions. Consistent with our previous findings in grass rats housed in winter- or summer-like lighting conditions [ 54 , 90 ] or following a BLT paradigm [ 52 ], the effects of BLT are brain region-specific and differ between males and females. The results from our present and previous studies provide novel insights into how seasonal light conditions and light therapy influence a variety of neural functions including neuropeptides and neurotransmitter systems, neuroinflammation, and neuroplasticity with concomitant effects on numerous behavioural outcomes highly relevant to SAD and other depressive disorders in humans [ 41 ].…”
Section: Discussionsupporting
confidence: 91%
“…In diurnal Nile grass rats, the levels of orexin-A and orexin immuno-reactive neurons was increased at night and in animals housed in bright light compared to dim. Additionally, bright light environments resulted in an increased protein expression of both orexin receptors in the medial prefrontal cortex in males compared to dim light [ 43 ]. These studies demonstrate orexin’s role in sleep-wake cycles in mammals, as well as the orexin response to stimuli, in addition to their influence on feeding behavior.…”
Section: Central Role Of Orexinmentioning
confidence: 99%